Disruption of the HLA-E/NKG2X axis is associated with uncontrolled HIV infections - Luis Romero-Martín; Luis Romero-Martín; Clara Duran-Castells; Clara Duran-Castells; Mireia Olivella; Míriam Rosás-Umbert; Marta Ruiz-Riol; Marta Ruiz-Riol; Jorge Sanchez; Dennis Hartigan-O´Connor; Dennis Hartigan-O´Connor; Beatriz Mothe; et al. (Frontiers in Immunology, 2022)
The contribution of the HLA-E/NKG2X axis in NK-mediated control of HIV infection remains unclear. We have studied the relationship between HLA-E expression and phenotypical as well as functional characteristics of NK cells, in the context of chronic HIV infection and in an in vitro model of acute infection. High viremia in HIV+ individuals was related to increased HLA-E expression, and changes in NK subpopulations, especially a reduction of the CD56bright as well as an increase in adaptive NK subpopulation. Uncontrolled HIV infection was also characterized by a reversion of the NKG2A/NKG2C expression ratio and a loss of positive and negative regulation of NK mediated by HLA-E. This was reflected in a lower cytotoxic, degranulation and cytokine production capacity, especially in CD56bright and adaptive NK. In line with these results, HLA-E expression showed a positive correlation with viral growth inhibition in an in vitro model of acute infection at day 7, which was lost after 14 days of culture. Using HLA-E expressing K562 cells, we determined that only one out of 11 described HIV-derived HLA-E epitopes increased HLA-E surface stability. In spite of that, eight of the 11 epitopes were capable of increasing degranulation and three drove differences in NK-cell mediated cell lysis or cytokine secretion. In conclusion, our results indicate that HLA-E molecules presenting HIV-derived epitopes may sensitize target cells for NK lysis in early HIV infection. However, prolonged exposure to elevated HLA-E expression levels in vivo may lead to NK cell dysfunction and reduced viral control In chronic infection.